If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 36 = 12x + -20 Reorder the terms: 36 + 8x = 12x + -20 Reorder the terms: 36 + 8x = -20 + 12x Solving 36 + 8x = -20 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 36 + 8x + -12x = -20 + 12x + -12x Combine like terms: 8x + -12x = -4x 36 + -4x = -20 + 12x + -12x Combine like terms: 12x + -12x = 0 36 + -4x = -20 + 0 36 + -4x = -20 Add '-36' to each side of the equation. 36 + -36 + -4x = -20 + -36 Combine like terms: 36 + -36 = 0 0 + -4x = -20 + -36 -4x = -20 + -36 Combine like terms: -20 + -36 = -56 -4x = -56 Divide each side by '-4'. x = 14 Simplifying x = 14
| 4x+40=16 | | 3x+4y=3-2 | | 6(x-12)+5(x-13)=6 | | X+.6x=265 | | V=(a+4)(a-5)(2a) | | P=80-20q | | X-11=32 | | 4tanx+3=7 | | 9-2x=y | | 0.01x^2+0.03x-0.10=0 | | 6/14/tan | | 7(x-8)-8x-7=x+7-x-2 | | tanx=6/14 | | 17b=w | | 5x^3=40x^2-80x | | 2x+3=12x-76 | | -5x^3-40x^2-80x=0 | | 2x+3=412x-76 | | a^2-4ab+4b^2-81=0 | | 6(3x+1)-10x=22 | | 2x(3x+6)=2x+17 | | 64=8*a^3 | | (4-y)(4-y)+y^2=16 | | 5/6=2/0.6 | | 9x+-5y=3 | | 5v/6-12=8 | | -9*786x=7-0 | | 5y+9=10 | | 8w-(5w-8)=18+5w | | 3y/4=5/16 | | 10/4(x-1)=2-x | | 12x+9x+10=262 |